Postprandial fatty acid specific changes in circulating oxylipins in lean and obese men after high‐fat challenge tests. Issue 3 (14th October 2013) - Strassburg, Katrin; Esser, Diederik; Vreeken, Rob J.; Hankemeier, Thomas; Müller, Michael; van, John; van, Jolanda; van, Susan J.; Afman, Lydia A.; Jacobs, Doris M.
<x xml:space="preserve">Abstract</x> Scope Circulating oxylipins may affect peripheral tissues and are assumed to play an important role in endothelial function. They are esterified in triglyceride‐rich lipoproteins that are increased after a high‐fat (HF) meal, depending on BMI and fatty acid (FA) type. Yet, it is unclear which oxylipins appear in circulation after HF meals differing in FA composition. Methods and results In a double‐blind randomized crossover challenge study, we characterized the postprandial oxylipin response after different HF challenges in lean and obese men receiving HF milkshakes, either high in saturated FAs (SFA), monounsaturated FAs (MUFA), or omega 3 (n‐3) polyunsaturated FAs (PUFA). Plasma oxylipin profiles were significantly altered at 2 and 4 h after shake consumption when compared to baseline. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) derived oxylipins increased after n‐3 PUFA shake consumption. MUFA shake consumption increased levels of cytochrome P450 mediated oxylipins. SFA shake consumption led to strong increases in linoleic acid (LA) derived HODEs. No differences were observed between lean and obese individuals at baseline and after any shake consumption. Conclusion We are the first demonstrating acute effects on circulating oxylipins after HF meal challenges. These changes were strongly influenced by different dietary FAs and may affect endothelial function.